Penerapan Model Problem Based Learning dengan Media Powtoon untuk Meningkatkan Hasil Belajar Kimia - Putri Rarawati Dewi; Dahlan; Maysara (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2024)
The research “The Application of Problem Based Learning Model with Powtoon Media to Improve Chemistry Learning Outcomes” aims to determine the improvement of student’s chemistry outcomes taught using problem based learning model with powtoon media. This research method used is Pre-Experiment with one group pretest-posttest design. The subjects of this study were students of class XI MIPA 2 SMAN 8 Kendari which amounted to 24 people. Data collection techniques were carried out using research instruments in the form of multiple choice test of 20 questions, observation sheets, and students response questionnaires. The results shiwed that the average value of student learning outcomes was 78,23 with an average n-gain of 0,73, the average percentage of student learning activities and teacher teaching activities was 88,63% and 83,33% respectively or in the very good category, the average percentage of student responses to the application of problem based learning models with powtoon media was 76,42% or in the good category